2000
DOI: 10.1093/ije/29.3.536
|View full text |Cite
|
Sign up to set email alerts
|

How many data sources are needed to determine diabetes prevalence by capture-recapture?

Abstract: In a Western population, the only demographic data required for matching patients on lists used for CR methods are first name, family name and date of birth, if unique identifiers such as social security numbers are not available. Two lists alone do not produce reliable data, and at least three lists are needed to allow for modelling for 'dependence' between datasets. The use of more than three lists does not substantially alter the absolute value or confidence of enumeration, and multiple lists (if available)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…It has been shown that increasing the number of databases does not necessarily produce significant improvements in incidence estimates (Ismail et al, 2000). Nevertheless, four underlying assumptions must be satisfied in order to produce reliable and internally valid results Regal, 1992, 1995;Brenner, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that increasing the number of databases does not necessarily produce significant improvements in incidence estimates (Ismail et al, 2000). Nevertheless, four underlying assumptions must be satisfied in order to produce reliable and internally valid results Regal, 1992, 1995;Brenner, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the technique has been adopted in health studies of human populations to generate more accurate rates of disease and disability, including diabetes (Ismail et al, 2000), spinal cord injuries (Chiu et al, 1993), stroke (Taub et al, 1996) and HIV (Bernillon et al, 2000). The method has become increasing popular for estimating hidden populations, such as illicit drug users (Frischer et al, 1993) and the homeless (Fisher et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…An estimation of the total number of victims including missing cases was derived using the simplest form of a twosample capture-recapture model developed by someone [17][18][19]. Thus, drowning rates and CI (confidence interval) were calculated using the estimated total number of drowning cases (N) using the following formula:…”
Section: Capture-recapture Record Categorizationmentioning
confidence: 99%
“…For the purpose of this analysis, all the relevant studies ascertained were collapsed into three sources: electronic databases (e.g., MEDLINE, PEDRO), experts (e.g., Cochrane Muscloskeletal Injuries Group), and hand searching (e.g., reference lists, conference proceedings) meeting the inclusion criteria upto and including February 2002. We chose these three sources as it has been noted that a greater number of sources does not substantially alter the absolute value of the estimated number of missed studies [32]. With three data sources there are eight possible combinations of sources in which individual studies may or may not appear.…”
Section: Capture-recapturementioning
confidence: 99%